THE USE OF DISCOVERY METHOD TO IMPROVE STUDENTS’ WRITING ON DESCRIPTIVE TEXT AT THE 10th GRADE OF SMAN 1 SUNGGUMINASA - Annisa, Nur Inna; Nappu, Syamsiarna; Natsir, Ratu Yulianti (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2018)
The main point of this research was The Use of Discovery Method to Improve Students’ Writing on Descriptive Text (Pre-Experimental Research at the Tenth Grade of SMAN 1 Sungguminasa). The objective of the reseacrh was to find out whether using Discovery Method was able to improve the ability of the students’ of SMAN 1 Sungguminasa to write descriptive text. This research employed Pre-Exoerimental design that applied Discovery Method to taught writing descriptive text. The study had been done for eight meetings that were designedx; first meeting was for pre-test, 6 meetings for treatment, and the last meeting for post-test. The population was tenth grade students of SMAN 1Sungguminasa in academic year 2016/2017. Total number of population was 25 students and class X MIA 4 was taken as sample by using purposive sampling technique. As the Quantitative method the writer analyzed the data by using t-test. The result showed that there were significance difference on the students’ writing descriptive text in term of content and organization taught with Discovery Method. The students’ mean score of content was 48.8 in pre-test to be 79.6 in post-test. Then, the students’ mean score of organization was 38 in pre-test to be 58.8 in post-test. The study concluded that teaching writing by using Discovery Method increased the students’ ability to write descriptive text at the Tenth grade of SMAN 1Sungguminasa.